The Influence Of Employee Remuneration, Work Motivation, And Work Discipline On Employee Performance In The Langkat Regional Development Planning Agency - Rachman, Syaiful; Lubis, Lia Iriani; Nurhasanah, Nurhasanah; Iskandar, Ismed; Tarigan, Nur M.Ridha; Nasti, Nilawati (Economics and Digital Business Review, 2024)
This exploration intends to determine the impact of representative compensation, work inspiration and work discipline to some extent and, at the same time, worker execution at the Langkat Rule Provincial Improvement Arranging Organization. The examination was led at the Langkat Rule Territorial Improvement Arranging Organization, Jalan Tengku Amir Hamzah, Kwala Bingai, Stabat Locale, Langkat Regime, North Sumatra Territory, postal code 20811, with a population of 36 individuals and an exploration test of 34 individuals. Information assortment was completed through meetings, polls and documentation. Using version 24 of the IMB Statistics for Product and Service Solution (SPSS) computer program, multiple regression analysis was used to analyze the data. In light of the consequences of the examination, it is found that representative compensation meaningfully affects the presentation of workers of the Langkat Regime Provincial Improvement Arranging Organization. This is upheld by the outcomes investigation t count < t-table (2.899 > 2.045) at n = 34 at an importance level of 95%. Work inspiration affects the exhibition of representatives of the Langkat Regime Provincial Improvement Arranging Organization; this is upheld by the examination of t count > t-table (3.543 > 2.045) at n = 34 at an importance level of 95%. The analysis of t count > t-table (2.988 > 2.045) at n = 34 with a significance level of 95% demonstrates that employees of the Langkat Regency Regional Development Planning Agency experience a positive and significant effect of work discipline on their performance. The value of F-count > F table (16.012 > 2.92) indicates that employee remuneration, work motivation, and work discipline have a positive and significant impact on employee performance at the Langkat Regency Regional Development Planning Agency.